2002
DOI: 10.1021/jo026369j
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Synthesis of Tetraalkylureas from Secondary Amines and Carbon Dioxide

Abstract: The reaction of dialkylamines with CO(2) giving tetraalkylureas can be performed at 60 degrees C. The reaction requires CCl(4), is weakly promoted by DMAN or PPh(3), and is not promoted by a Pd catalyst. A two-step procedure, in which dialkylammonium dialkylcarbamate is produced in situ and then reacted with CCl(4) and free dialkylamine, gave greater yields of urea than a simple single-stage procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The results of these trials revealed an independence of the reaction velocity from CO 2 pressure within the tested pressure range ( Table 2). at 60°C and 30 bar (Table 2, Entries 3,8,9). [34,55,60] Reaction temperatures evaluated ranged from room temperature up to 80°C (30 bar, [Cat]:[CoCat] = 1:1).…”
Section: Coupling Reactions Of Co 2 and Epoxidesmentioning
confidence: 99%
“…The results of these trials revealed an independence of the reaction velocity from CO 2 pressure within the tested pressure range ( Table 2). at 60°C and 30 bar (Table 2, Entries 3,8,9). [34,55,60] Reaction temperatures evaluated ranged from room temperature up to 80°C (30 bar, [Cat]:[CoCat] = 1:1).…”
Section: Coupling Reactions Of Co 2 and Epoxidesmentioning
confidence: 99%
“…To date, two compounds synthesized from CO 2 have industrial importance: salicylic acid has been prepared for over a century [14,15] and urea is prepared from CO 2 on a 100 million ton scale per annum. [16][17][18] Another commercially important process is the production of polymeric and cyclic carbonates. [8,[19][20][21] Cyclic carbonates can be used as intermediates for polycarbonates, [22,23] [a] WACKER- Lehrstuhl dependence on catalyst concentration.…”
Section: Introductionmentioning
confidence: 99%
“…All those results suggested that the N-substituted carbamates could be successfully synthesized from the aliphatic amines, urea and 40 alcohols. Then, the reaction of various aromatic amines, urea and ethanol was also studied (entries [11][12][13][14][15][16]. Under the optimized reaction conditions, 73% conversion of aniline was obtained (entry 11), which could be ascribed to the weaker basicity of the 45 aromatic amine.…”
Section: N-substituted Carbamates Syntheses From Various Amines Ureamentioning
confidence: 99%
“…In this context, 25 exploration of alternative ways for CO 2 activation and utilization in large scale are highly desired. Until now, manufacturing urea is very mature [13][14][15] and currently global supply of urea is exceeding demand, especially in China. In this sense, using urea as feedstock to produce higher valuable chemicals opens a new 30 window for CO 2 utilization and alternative carbonyl sources to substitute phosgene, e.g., manufacturing of carbonates and Nsubstituted carbamates via direct CO 2 activation are very difficult, while using urea to produce carbonates [16][17][18][19][20][21][22] and N-substituted carbamates are very efficient and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation